2016
DOI: 10.3151/jact.14.87
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity and Chloride Ingress in Hardened Cement Paste

Abstract: The transport properties of hardened cement paste (HCP) have been investigated in many studies; the AC impedance method (ACI) is a non-destructive technique employed for this purpose and has been used in investigations of the electrical characteristic and mass transport properties of HCP. However, there are relatively fewer studies investigating chloride ingress in HCP and using the ACI. In this study, the relationship between the electrical conductivity measured by the ACI and chloride ingress was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…using impedance measurements (Kurumisawa and Nawa 2016) or similar to our work -deriving resistivity based on recorded resistance values (McCarter et al 2001). The electrical resistivity of mortar in this work was measured using the "2-pin method" where the "pins" were initially cast-in brass plates with dimensions equal to the sides of the mortar cubes (i.e.…”
Section: Mortar Electrical Resistivitymentioning
confidence: 99%
“…using impedance measurements (Kurumisawa and Nawa 2016) or similar to our work -deriving resistivity based on recorded resistance values (McCarter et al 2001). The electrical resistivity of mortar in this work was measured using the "2-pin method" where the "pins" were initially cast-in brass plates with dimensions equal to the sides of the mortar cubes (i.e.…”
Section: Mortar Electrical Resistivitymentioning
confidence: 99%
“…The electrical conductivity and microstructure of cement paste over a range of water to cement ratios was investigated in the study [8]. It was shown that it is possible to predict the chloride ingress by measurements of the electrical conductivity.…”
Section: Methodology Selection Justificationmentioning
confidence: 99%
“…However, as Diamond [11] noted, the 39 pore size distribution obtained by MIP is not a true pore size distribution because of ink-bottle effects; 40 the validity of using a total porosity with certain maximum and minimum pore sizes is unclear. 41 Hamami et al [12] used the main pore diameter D c , defined as the mean value of the normal 42 distribution fitted on the main peak of a pore size distribution, as an indicator of the pore structure and 43…”
Section: Introduction 27mentioning
confidence: 99%
“…4. The porosity measured by 208 MIP is lower than that measured by the weight difference between water-saturated and oven-dried 209 samples [40][41][42]. The determination coefficient of the air permeability coefficient and total pore 210 volume is very low at 0.07.…”
Section: Introduction 27mentioning
confidence: 99%